Nature and Art - Inchbald, Mrs., 1753-1821; Morley, Henry, 1822-1894 (Salt Lake City, UT : Project Gutenberg, 2003)
"Nature and Art" by Mrs. Inchbald is a novel published in 1796. This satirical fable follows two generations of the Norwynne family, tracing how education, privilege, and social conventions shape human behavior. Two brothers take vastly different paths$1 (Bone through music, one through the church$1 (Bleading to estrangement and reconciliation. Their sons, bearing the same names, inherit contrasting upbringings that expose the corrupting effects of England's social system. Through paired opposites, Inchbald delivers a blunt critique of institutional oppression and women's place in society. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Nature_and_Art
Release date is 2003-02-01
Transcribed from the 1886 Cassell & Co. edition by David Price
Keywords: Inchbald, Mrs., 1753-1821; Fathers and sons -- Fiction; Young women -- Fiction; Domestic fiction; Epistolary fiction; Brothers -- Fiction